2016
DOI: 10.1161/circulationaha.115.017923
|View full text |Cite
|
Sign up to set email alerts
|

Vasodysfunction That Involves Renal Vasodysfunction, Not Abnormally Increased Renal Retention of Sodium, Accounts for the Initiation of Salt-Induced Hypertension

Abstract: Prevailing theory holds that abnormally large increases in renal salt retention and cardiac output are early pathophysiologic events mediating initiation of most instances of salt-induced hypertension. This theory has come under increasing scrutiny because it is based on studies that lack measurements of sodium balance and cardiac output obtained during initiation of salt-loading in proper normal controls, i.e., salt-resistant subjects with normal blood pressure. Here we make the case for a “vasodysfunction” t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
108
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 139 publications
(232 reference statements)
4
108
1
1
Order By: Relevance
“…2 However, the dissociation of salt-induced changes in blood pressure from salt-induced changes in blood volume could be explained by alterations in vascular resistance that may not necessarily depend on alterations in renal or extra-renal sodium handling. 19, 57 Normal salt-resistant subjects, acutely 2034, 41, 42, 45, 46 and chronically, 27, 40, 47, 49, 50 can sustain large salt-induced increases in sodium balance, blood volume, and cardiac output without increases in blood pressure because they vasodilate and substantially reduce vascular resistance in response to high salt diets. 19, 24, 25, 41, 45, 46, 49, 50 Thus, in normal individuals, resistance to the pressor effects of acute or chronic increases in salt intake is not usually due to an ability to rapidly excrete a salt load and prevent substantial increases in sodium balance, blood volume, and cardiac output.…”
Section: In Normal Individuals How Can Acute and Chronic Increases Imentioning
confidence: 99%
See 2 more Smart Citations
“…2 However, the dissociation of salt-induced changes in blood pressure from salt-induced changes in blood volume could be explained by alterations in vascular resistance that may not necessarily depend on alterations in renal or extra-renal sodium handling. 19, 57 Normal salt-resistant subjects, acutely 2034, 41, 42, 45, 46 and chronically, 27, 40, 47, 49, 50 can sustain large salt-induced increases in sodium balance, blood volume, and cardiac output without increases in blood pressure because they vasodilate and substantially reduce vascular resistance in response to high salt diets. 19, 24, 25, 41, 45, 46, 49, 50 Thus, in normal individuals, resistance to the pressor effects of acute or chronic increases in salt intake is not usually due to an ability to rapidly excrete a salt load and prevent substantial increases in sodium balance, blood volume, and cardiac output.…”
Section: In Normal Individuals How Can Acute and Chronic Increases Imentioning
confidence: 99%
“…19, 57 Normal salt-resistant subjects, acutely 2034, 41, 42, 45, 46 and chronically, 27, 40, 47, 49, 50 can sustain large salt-induced increases in sodium balance, blood volume, and cardiac output without increases in blood pressure because they vasodilate and substantially reduce vascular resistance in response to high salt diets. 19, 24, 25, 41, 45, 46, 49, 50 Thus, in normal individuals, resistance to the pressor effects of acute or chronic increases in salt intake is not usually due to an ability to rapidly excrete a salt load and prevent substantial increases in sodium balance, blood volume, and cardiac output. 19 Rather, it may be due to reductions in systemic vascular resistance in response to acute and chronic salt-loading 19, 24, 25, 41, 45, 46, 49, 50 mediated largely, or only by, reductions in renal vascular resistance.…”
Section: In Normal Individuals How Can Acute and Chronic Increases Imentioning
confidence: 99%
See 1 more Smart Citation
“…The theory holds that abnormal pressure natriuresis causes sustained salt-induced hypertension by causing abnormal increases in CO that are too small to be detected. 9,13,14,28 These observations add to growing concerns 15,27,[31][32][33][34][35][36][37] about the pressure natriuresis theory of chronic hypertension. Accordingly, we anticipate that this theory, advanced through the pioneering efforts of Arthur Guyton and others, 4,5,13,[38][39][40][41][42] will eventually be replaced by testable theories about the abnormalities that initiate hypertension and cause it to be sustained.…”
Section: Can the Pressure Natriuresis Theory Of Chronic Hypertension mentioning
confidence: 96%
“…26 Importantly, and in direct opposition to these statements, at no time during the initiation or maintenance of salt-induced hypertension has it been found that CO is greater in salt-loaded salt-sensitive subjects than in saltloaded normal controls. 27 To address this fact, the proponents of the pressure natriuresis theory contend that the abnormal increases in CO are too small to detect. 9,13,14,28 For example, it is stated that: "The long-term elevation in cardiac output is so slight that usual methods for measuring cardiac output are not adequate to prove that it is indeed elevated."…”
Section: Can the Pressure Natriuresis Theory Of Chronic Hypertension mentioning
confidence: 99%